Visual Artist or Visual Designer? Visual Communication Design Education - Arsoy, Aysu (Eastern Mediterranean University (EMU), 2010)
ABSTRACT: Design tools and contents have been digitalized, forming the contemporary fields of the visual arts and design. Corporate culture demands techno-social experts who understand the arts, design, culture and society, while also having a high level of technological proficiency. New departments have opened offering alternatives in art and design education such as Visual Communication Design (VCD) and are dedicated to educating students in the practical aspect of using digital technologies in visual design. The aim of this research is to investigate the current adoption and understanding of VCD education in Turkey and North Cyprus. The marketing and commercialization strategies of various institutes are analyzed to reflect the trends and possible invisible curricula present in VCD. VCD students profiles were examined and interviews were conducted in order to understand the purpose of VCD education from the students’ and VCD scholars’ perspective. Questionnaires were also administered to VCD students in order to determine if future visual designers are aware of the complexities of the actual elements of visual design. The cognitive portion of this research demonstrates the difference between vision and perception which is one of the major subjects in VCD. The differences are demonstrated through the use of methods borrowed from critical pedagogy and semiotics in order to analyze this relatively new field in education. Various triangulation approaches were used to analyze the perceptions of students and scholars and synthesize suggestions to improve VCD curriculum. Keywords: Visual Communication, Design, Artist, Designer, Education. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Çağdaş görsel sanatlar ve tasarım alanlarında, hem tasarım araçları ve hem de içerik olarak sayısal ortamda uygulamalar üretilmektedir. Görsel tasarım alanında kurumsal kültür, sanat ve tasarım, kültür ve toplum aynı zamanda teknoloji becerileri olan tekno-sosyal uzmanlar talep etmektir. Görsel İletişim Tasarımı (GİT) gibi alternatif sanat ve tasarım eğitimi veren bölümler de, görsel tasarım uyulamarında sayısal teknolojiler kullanarak bu özelliklere sahip öğrenciler yetiştirmeyi amaçlamaktadır. Bu araştırmada, Türkiye ve Kuzey Kıbrıs’da GİT eğitiminin benimsenmesi ve anlayışı iredelenmektedir. GİT’deki görünmeyen müfredat ve eğilimlerini yansıtmak için enstitülerin pazarlama ve ticari stratejileri incelenir. Öğrenciler ve akademisyelerin GİT’e bakış açılarını - GİT öğrenci profilleri incelenerek GİT eğitiminin amacı nedir?- yansıtan görüşmeler gerçekleştirildi. Ayrıca GİT öğrencilerine anket uygulanmıştır. Geleceğin görsel tasarımcıları, görsel tasarım unsurlarının karmaşıklığını farkında mı? Araştırmanın bilişsel bölümü ise görme ve algı arasındaki farklara değinerek, görme ve algının GİT’deki önemini yansıtır. Eğitimdeki bu yeni alan incelenirken, eleştirel pedagoji ve göstergebilim yöntemlerini kullanıldı. Çeşitli nirengi yaklaşımlarla öğrenci ve akademisyenlerin görüşleri GİT müfredatını geliştirmek için öneriler sunmaktadır. Anahtar Kelimeler: Görsel İletişim, Tasarım, Sanatçı, Tasarımcı, Eğitim.
Doctor of Philosophy in Communication and Media Studies. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Communication and Media Studies, Dept. of Communication and Media Studies, 2010. Supervisor: Assist. Prof. Dr. Ümit İnatçı.
Keywords: Communication and Media Studies; Visual Communication; Communication in Design; Visual Communication - Design - Artist - Designer - Education